Antioxidant and antimicrobial activities of fruit juices and pomace extracts against acne-inducing bacteria - Ördögh, Lilla (Acta Biologica Szegediensis, 2010)
Acne vulgaris is the most common skin disease in the world, and the number of antibiotic resistant acne-inducing bacterial strains has been increasing in the past years. Natural substances from plants are promising candidates to treat this disease. In the present study, in vitro biological activity of the juice, as well as water and methanol extracts of the pomace, of 20 cultivated and wild fruits was investigated on 4 acne-inducing bacteria (Propionibacterium acnes, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes). The MIC values of juices and pomace extracts (water and methanol) were determined by broth microdilution assays at pH 7 and at skin neutral pH 5.5. Total phenol content and radical scavenging capacity of the active juices and extracts was also determined. Red and purple berries revealed a substantial antibacterial and antioxidant effect but there was no strong correlation between the antioxidant and antimicrobial properties. Staphylococcus strains were the most sensitive to the juices, and S. pyogenes, to the methanol extracts. Among the bacteria tested, P. acnes proved to be the most insensitive species in this study. The growth inhibition effect of Ribes uva-crispa (gooseberry) juice was stronger at acidic pH (MIC 0.40 mg/ml) than at neutral pH (MIC 5.30 mg/ml). The antibacterial effect of the other fruits and berries showed no significant difference at the different pH values.